Nutritive value and metabolic effects of whey protein concentrate and hydrolysed lactose for growing pigs - Näsi, Matti (Agricultural and Food Science, 1984)
In two digestibility and balance trials with growing pigs, whey protein concentrate (WPC) was compared as a protein supplement with casein (CAS) and dried skim milk (DSM), and, 30 % lactose (40 % dried whey, DW) was compared as a sugar supplement with the same amounts of hydrolysed lactose (HYLA) and sucrose (SUC). The effects of these supplements on protein and mineral metabolism of the pigs were investigated, WPC contained 42.2 % crude protein and had a high content of lysine, 8.6 g, and sulphur containing amino acids: cystine 2.8 and methionine 2.2g/16 g N, These exceeded the values for DSM. The hydrolysing degree of the enzymatically treated lactose syrup was 73 %. WPC had high crude protein digestibility, 99.1 % as compared to 95.4 for CAS and 95.0 % for DSM. Dried whey had low crude protein digestibility, 72.5 %. The amino acids in the WPC diet were highly digestible, but low values were obtained for the DW diet. On the WPC diet, nitrogen retention was higher than with the other protein supplements (P > 0.05), urinary urea excretion was low and the biological value very high. On a combination of WPC and HYLA protein utilisation was higher than on dried whole whey. On the diets supplemented with different sugars, none of the blood parameters differed statistically significantly (P > 0.05) and all values lay within the reference range. Water intake was on average 49 % greater on diets with sugar supplements than without. Urinary excretion of reducing sugars averaged 40.2, 8.3 and 6.6 g/d on the HYLA, SUC and DW diets, while on the diets without sugar supplements the values were 0.8—1.2 g/d. The following mean daily mineral retention values were obtained: P 4.0 g, Ca 5,9 g. Mg 0,4 g, Na 1.9g, K 2.9 g, Fe 27 mg, Cu 6.4 mg, Zn 65 mg and Mn 4.0 mg. The surplus Na and K on the DW diet were excreted in the urine and the pigs did not have diarrhoea.